2018
DOI: 10.1002/npr2.12032
|View full text |Cite
|
Sign up to set email alerts
|

Roles of noradrenergic transmission within the ventral part of the bed nucleus of the stria terminalis in bidirectional brain‐intestine interactions

Abstract: Aims The bed nucleus of the stria terminalis (BNST) is a limbic structure mediating autonomic and neuroendocrine responses and negative affective states such as anxiety and fear. We previously demonstrated that noradrenergic transmission via β‐adrenoceptors within the ventral part of BNST (vBNST) is involved in bidirectional interactions between the brain and the upper gastrointestinal (GI) tract. The present study aimed to examine the roles of intra‐vBNST noradrenergic transmission via β‐adrenoceptors in bidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Fendt et al showed that NA release in the BNST was strongly increased during exposure to trimethylthiazoline (TMT), a component of fox odor. More recently, we showed that distension of gastrointestinal tract increased extracellular NA levels in the vBNST . These findings suggest that stimulations that induce negative emotions increase NA release in the vBNST.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Fendt et al showed that NA release in the BNST was strongly increased during exposure to trimethylthiazoline (TMT), a component of fox odor. More recently, we showed that distension of gastrointestinal tract increased extracellular NA levels in the vBNST . These findings suggest that stimulations that induce negative emotions increase NA release in the vBNST.…”
Section: Discussionmentioning
confidence: 58%
“…More recently, we showed that distension of gastrointestinal tract increased extracellular NA levels in the vBNST. 5,6 These findings suggest that stimulations that induce negative emotions increase NA release in the vBNST.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Also, microinjection of noradrenaline into the Me caused significant cardiovascular changes (Fortaleza et al, 2011 ). The Ce and BNST are involved in visceral hypersensitivity in visceral nociception (Su et al, 2015 ; Ide et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%